The Effectiveness of Giving Cold Compress in Pain Reduction Intensity of Perineal Wound of Postpartum Mother - Maria Ulfa; Laily Prima Monica (STIKes Patria Husada Blitar, 2020)
Perineal wound pain is very likely to cause problems for the postpartum mothers. In the process of childbirth often occurs perineal wound, for some cases, it will heal permanently, but if the wound is wide enough can be sutured to the perineum. Perineal repair not only giving some benefits, but also can cause pain. One way to deal is by applying non-pharmacological pain management, the way is by giving cold compresses in the form of ice bags, it will result smaller risk. The purpose of this study was to provide cold compress therapy in scars to reduce pain. Methods: Posttest only control group design. The population in this study was 30 postpartum mothers in Kanigoro Health Centers by using purposive sampling. The sample was 16 respondents. The independent variable was cold compress, while the dependent variable was pain in the perineal wound. The instrument used Standart Operating Prosedure.Â Results: Fisher Exact Probability Test shows p = 0.003 (a = 0.05).Â It could be concluded that giving cold compress could reduce the problem in perineal wound for postpartum mothers in the Kanigoro Health Center area. Along with this study, respondents are expected to actively ask questions, learn about problems during and after giving birth, especially not only learn about the technique of giving cold compresses to the perineum, but also about the provided comments.